2011
DOI: 10.1590/s0004-282x2011000200014
|View full text |Cite
|
Sign up to set email alerts
|

Neurological diagnoses in the emergency room: differences between younger and older patients

Abstract: Neurological diseases are prevalent in the emergency room (ER). The aim of this study was to compare the neurological diagnoses between younger and older patients evaluated in the ER of a tertiary care hospital. Method: Patients admitted to the ER who required neurological evaluation in the first 24 hours were separated into two groups based on age, ≤50 years old and >50 years old. Results: Cerebrovascular disease (59.6% vs. 21.8%, p<0.01) was most frequent in the >50 years old group. Seizures (8.1% vs. 18.6%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
(13 reference statements)
1
8
0
5
Order By: Relevance
“…in 2011 from Brazil shows CVD (42.69%), primary headache (7.1%), and seizure disorder (12%). [2] Furthermore, one more study by Carroll and Zajicek from the UK showed that stroke, headache, multiple sclerosis, and seizures were the most common emergency care patients and it accounted for 63% of cases. [4] Another study from Spain report most frequent diagnoses made were a headache, stroke, and epilepsy and accounted for 39% of emergency neurology care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in 2011 from Brazil shows CVD (42.69%), primary headache (7.1%), and seizure disorder (12%). [2] Furthermore, one more study by Carroll and Zajicek from the UK showed that stroke, headache, multiple sclerosis, and seizures were the most common emergency care patients and it accounted for 63% of cases. [4] Another study from Spain report most frequent diagnoses made were a headache, stroke, and epilepsy and accounted for 39% of emergency neurology care.…”
Section: Discussionmentioning
confidence: 99%
“…This shows seizure disorder, stroke is common across the world, and metabolic encephalopathy and head injury were unusually more common at our center compared with the other centers in the world. [234510] It may be due to the following reasons (1) referral bias of general medical causes causing encephalopathy (2) unknown patients subgroup (3) it is tertiary care and referral center for neuropsychiatry care rather than a multispecialty general hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No Brasil, um estudo demonstrou que as emergências neurológicas mais comuns são: acidente vascular encefálico, epilepsia, cefaleia e outros sintomas secundários à condição clínica. Este mesmo estudo mostrou ainda que 11% dos pacientes atendidos na emergência precisaram de uma avaliação neurológica (6) .…”
Section: Introductionunclassified
“…4 Em outro estudo que teve como objetivo comparar diagnósticos neurológicos entre pacientes jovens e idosos atendidos na unidade de emergência de um hospital terciário, constatou-se como diagnóstico mais comum as doenças cerebrovasculares (59,6%) nos pacientes maiores de 50 anos. 10 Resultados semelhantes foram verificados em nosso trabalho: quanto maior a faixa etária, maiores as emergências clínicas com causas neurológicas.…”
unclassified